Mensuração do grau de uso corporativo e repercussão nas mídias sociais: um estudo do setor hoteleiro - Scolaro, Maqueli (Universidade do Vale do Rio dos Sinos, 2016)
The emergence of Web 2.0 introduced an alternative channel for marketing communication between companies and their consumers, including platforms that are constantly modified by its users, such as social media. These online platforms are present in the day-to-day life of individuals and organizations and became for many companies the primary means of brand communication and communication with their clients. Identifying this reality for the hospitality industry of Serra Gaúcha, this study aims to measure the degree of Corporate Use and Impact on Social Media (GUCRMS) of selected establishments through a survey of activities in social media and the reactions generated in their followers. For the application of the research, there was a survey of 85 hotels data located in Serra Gaúcha and from five social media, Facebook, Twitter, Instagram, Google+ and YouTube. The results show that the hotels in Serra Gaúcha do not tend to work in a group of social media, but, within two online platforms, highlighting the socials media Facebook and Twitter that have the highest impact factor for the analyzed sector. In addition, it was found that Facebook followers are more likely to enjoy and share the publications generated by establishments compared to other social media. Finally, it was noted that the analyzed establishments have mostly low GUCRMS (51% of the sample), followed by establishments that have strong and medium GUCRMS with 28% and 21% of the sample respectively. With the results we can conclude that the measurement of GUCRMS helps in directing the activities of the establishments, assisting in the identification of online platforms with high impact factors and hotels that serve as reference performance and effect on online platforms wider audience.
Keywords: Comunicação de marketing; Mídias sociais; Fator de impacto das mídias sociais; Grau de uso corporativo e de repercussão; Marketing communications; Social media; Factor impact of social media; Degree of corporate social use and impact; ACCNPQ::Ciências Sociais Aplicadas::Administração